Molecular and morphological studies identify a new genus within the Heterolepismatinae (Zygentoma: Lepismatidae) - Smith, Graeme B.; Mitchell, Andrew; Molero-Baltanás, Rafael (Zootaxa, 2021)
Molecular studies using COI and 28S sequence data strongly identify a clade within the Heterolepismatinae distinct from the majority of species so far sequenced. The independence of the clade is supported by several morphological characters including a glabrous anterior margin to the frons, large trapezoidal thoracic sternites, tarsal trichobothria, long, conical parameres which in some species consist of two segments, and the presence of triangular or rounded subrectangular scales on the femora, tibia and clypeus. This clade is described as a new genus Visma n. gen. containing ten new species V. advenum n. sp., V. bingara n. sp., V. brayi n. sp., V. bundjalung n. sp., V. brigalowsum n. sp., V. capricornia n. sp., V. pallidum n. sp., V. powellheueri n. sp., V. tenebrosum n. sp. and V. xanthorrhoea n. sp.. Heterolepisma stilivarians Silvestri, 1908 is redescribed from the holotype and transferred to the new genus. The remaining H. stilivarians type series is found to be different to the holotype and removed from the type series. It is considered possible that H. annectens Silvestri, 1924 may also belong to this genus. Scanning electron microscopy of scale shape and rib-spacing is shown to be a useful tool to separate at least some species of the genus and considered to have greater potential if well preserved material is available.